2015
DOI: 10.1002/mrm.25773
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating t cartilage imaging using compressed sensing with iterative locally adapted support detection and JSENSE

Abstract: Purpose To accelerate T1ρ quantification in cartilage imaging using combined compressed sensing with iterative locally adaptive support detection and JSENSE. Methods To reconstruct T1ρ images from accelerated acquisition at different time of spin-lock (TSLs), we propose an approach to combine an advanced compressed sensing (CS) based reconstruction technique, LAISD (Locally-Adaptive Iterative Support Detection), and an advanced parallel imaging technique, JSENSE. Specifically, the reconstruction process alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 47 publications
0
65
0
Order By: Relevance
“…In addition, the relatively low resolution of T 1ρ and T 2 images (0.6 mm in plane with 4 mm slices) may introduce bias to T 1ρ and T 2 values due to the partial volume effect. Advanced acceleration techniques can be applied in the future to obtain T 1ρ and T 2 images with higher resolutions within clinically acceptable acquisition time (27). The reproducibility was evaluated only in healthy controls and should be evaluated in OA subjects in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the relatively low resolution of T 1ρ and T 2 images (0.6 mm in plane with 4 mm slices) may introduce bias to T 1ρ and T 2 values due to the partial volume effect. Advanced acceleration techniques can be applied in the future to obtain T 1ρ and T 2 images with higher resolutions within clinically acceptable acquisition time (27). The reproducibility was evaluated only in healthy controls and should be evaluated in OA subjects in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that sparse reconstructions can be used for faster and yet accurate quantitative sodium imaging of knee cartilage at 7T, opening the door for sodium imaging-based quantitative assessment of osteoarthritis 170 . Quantification of T 1ρ similarly holds promise for characterization of osteoarthritis, and acceleration of T 1ρ mapping in the knee has been demonstrated in early feasibility studies 171,172 . Accelerated dynamic functional metabolic imaging of phosphocreatine kinetics after calf muscle exercise has also been shown for 3D 31 P spectroscopic imaging at 7T 173 .…”
Section: Clinical Applications Of Sparse Reconstruction Techniquesmentioning
confidence: 99%
“…a. This sampling pattern was used previously . Since many relaxation‐weighted images have to be captured to reconstruct relaxation maps, the acquisition process is repeated several times.…”
Section: Review Of Cs Mri For Compositional Mappingmentioning
confidence: 99%
“…The reconstruction problem can be formulated as: bold-italicx^=argminbold-italicxyExbold2bold2+λR(bold-italicx), where x is a vector that represents the reconstructed set of relaxation‐weighted images, with its original size of Ny×Nz×p, y is a vector that represents the captured k ‐space data for all relaxation‐weighted images, its original size is k y × k z × c × p , where c is the number of receive coils, and the matrix E represents the encoding matrix mapping x to y , containing coil sensitivities (when parallel imaging and CS is jointly used, Fourier transforms, and sampling pattern . Many CS methods for knee cartilage use the joint parallel imaging and CS approach to achieve higher undersampling rates, as shown previously . The use of squared l 2 ‐norm, or Euclidean norm, bold-italice 22=i=1N| ei |2, is quite common either because it is related to the usual assumption of Gaussian noise, or because it leads to a more tractable mathematical problem.…”
Section: Review Of Cs Mri For Compositional Mappingmentioning
confidence: 99%
See 1 more Smart Citation